EXPERIÊNCIAS ACADÊMICAS EM UMA UNIDADE DE ESTRATÉGIA DA SAÚDE DA FAMÍLIA - Kolankiewicz, Adriane C. B.; Scarton, Juliane; Scarton, Juciane; Mertins, Simone M.; Mayer, Bárbara L. D.; Wildner, Laura E. S. (Salão do Conhecimento, 2013)
Resumo